Regional sea level change study based on estuarine sediment color and biogeochemistry - preliminary results - Mestre, Nélia (2013)
Coastal zones play a significant role in the regional development and have been an important area for human occupation through time. The study of estuarine sediments applied to sea level changes had always been of extreme importance, as it reflects the coastal line evolution, either by local, regional or global changes.